Evaluation of the quality of life and burnout syndrome in university professors - Melo Miranda, Isabela Maria (2021)
The expression quality of life involves objective and subjective parameters, such as health and other factors, and its understanding is somewhat individual and dynamic. Teachers, due to their work dynamics, are prone to develop Burnout Syndrome and have their quality of life negatively affected. Objective: To evaluate the presence of Burnout Syndrome among professors of an undergraduate medical course and its correlation with quality of life. Methods: Cross-sectional study with higher education teachers, by assessing sociodemographic and behavioral characteristics, quality of life by the WHOQOL-bref and the presence of Burnout by the Maslach Burnout Inventory - Educators Survey. In addition to the descriptive analysis, the intraclass correlation coefficient (ICC), Cronbach's alpha and Pearson's correlation coefficient were used. Results: The results of the 22 participants showed a majority of male teachers, with an average age of 36.4 years, married and working as a teacher, on average, 29.5 hours per week. A negative correlation was identified between exhaustion and the physical (p = 0.005), psychological (p = 0.015) and general (p = 0.009) domains, suggesting a reduction in quality of life; and a positive correlation between professional effectiveness and psychological domain (p = 0.023), suggesting that the positive perception of professional effectiveness raises QOL among teachers. Conclusion: The prevalence of Burnout syndrome among university professors was low, although factors that interfere in QOL, both positive and negative, have been identified. The findings can assist in understanding the characteristics of this audience and in the development of preventive strategies for these conditions.Keywords: quality of life; faculty; mental health